The role of disaccharides for protein–protein interactions – a SANS study. (17th November 2019) - Olsson, Christoffer; Swenson, Jan
ABSTRACT: The disaccharide trehalose has shown outstanding anti-aggregation properties for proteins, which are highly important for the possibility to treat neurodegenerative diseases, such as Alzheimer's and Huntington's disease. However, the role and mechanism of trehalose for such stabilising effects are still largely unknown, partly because a direct structural picture of how trehalose organises around proteins in an aqueous system is missing. Here we compare small-angle neutron scattering (SANS) data on myoglobin in aqueous solutions of either sucrose or trehalose, in order to investigate their effect on protein–protein interactions. We find that both trehalose and sucrose induces a well-defined protein–protein distance, which could explain why these inhibit protein–protein interactions and associated protein aggregation. It does not however explain the superior anti-aggregation effect of trehalose and suggests that the local solvent structures are highly important for explaining the protein stabilisation mechanism. In a broader perspective, these findings are important for understanding the role of sugars in biological stabilisation, and could provide a structural explanation for why trehalose is a promising candidate for the treatment of neurodegenerative and other protein aggregation related diseases. GRAPHICAL ABSTRACT: